Reiki: a modality towards holistic approach to cancer cure - Puri, Sonia; Walia, Dinesh Kumar; Jindal, Har Ashish (International Journal Of Community Medicine And Public Health, 2017)
Reiki is one of the complementary and alternative medicine modalities which have been accepted and appreciated, globally. Many evidence based studies have validated its role in cancer. Reiki can play a major role in changing the patient’s outlook towards life and increasing the patient’s ability as well as willingness to comply with physician’s instructions and adhere to treatment protocols. The goal of Reiki treatments is to strengthen the flow of energy through these blocked or disturbed pathways, thus decreasing pain and enhancing the body’s natural ability to fight illnesses and heal itself. It combats the nausea caused from chemotherapy. One of the major criticism is lack of scientific foundation. There has been effort to collaborate conventional and complementary therapies to improve the quality of future research. In the near future, it may be considered as one of the advanced modalities of alternative medicine used in conjunction with conventional therapy for holistic approach for cancer management.